Development of hydropave asphalt mixture for malaysian roads - Chuah, Pooi Yee (2014)
Wet condition roads has been one of the contributing factor of accidents, this is especially critical for countries such as Malaysia that receives rain all year round. The decrease on friction resistance, increase possibility of hydroplaning and reduce of sight visibility due to splashing ultimately increases the hazard of road users. In order to mitigate this problem, porous asphalt was introduced in Malaysia. The term porous asphalt represents high amount of air voids or percentage of voids in total mix (VTM) which was designed to drain off excessive runoff from pavement surface during storm. However, the application of porous asphalt is not very popular in Malaysia due to its costly mixed necessary to achieve required water drainage at the expense of higher ratio of coarse aggregates and lower binder viscosity. Thus, Hydropave asphalt mixture is developed in this study to overcome the said problem by implementing an effective drainage on road pavement. This technique is achieved by categorizing rainfall depths into different zones and by proposing a suitable cross fall as well as required air voids content in asphalt mixtures. Based on the Malaysia annual rainfall data for year 2000 to 2009, three different zones were categorized ranging from high to low. In order to achieve the optimum efficiency in terms of performance and cost for Hydropave asphalt mixture, the recommended VTM and cross fall established is then assigned to each zone. Laboratory experiments which included rainfall simulation on hydropave mixture slabs at different design VTM was conducted to obtain the relationship of variables in this study. Five hyropave asphalt slabs were designed based on five different air voids at 10%, 15%, 20%, 25% and 30%. Results for high rainfall zone found that the VTM required were from 20% to 23% as recommended cross fall for a maximum of 6% to a minimum of 2.5% inclination respectively in order to sufficiently drainoff the surface runoff. During moderate rainfall intensity, the required air voids to eliminate water ponding condition was lower when compared to high rainfall intensity zone which was 18% to 20% with corresponding flow rate of 230.3 to 389.5 cm3/s when applied on minimal cross slope of 2.5%, while asphalt mixture slab containing lower percentage of air voids at 14% to 18% would be sufficient when cross slopes of 3.0% to 6.0% is allowed. For lowest rainfall intensity zone, results shown that asphalt mixtures with air voids contents ranging 14% to 18% has no water ponding condition with fulfilling minimal cross slope requirement at 2.5% during rainfall simulation test.